Effects of upstream kishanganga hydropower project on hydrological plows and power generation capacity at Athmuqam and Neelum Jhelum HPP in Pakistan - Muhammad Ahsan Amjad (00000117424); Dr Kafait Ullah (USPCAS-E, NUST, Islamabad, 2017)
TH-70
Keywords: MS-ESE Thesis MS Thesis